Change management in higher education: unveiling employee responses at a regional state university in the Philippines - Fiedacan, Roy F.; Baldera, Philip R.; Villanueva, Emelyn R.; Ramos, Reynaldo P.; Ramos, Emelia B. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the perceptions and lived experiences of employees at Romblon State University (RSU) in response to organizational change and the influence of academic leadership. A hermeneutic phenomenological approach was applied involving 12 purposively selected employees from different campuses and academic ranks. Data collection methods included semi-structured interviews and focus group discussions (FGDs). Thematic analysis produced five themes: perceptions of change as a strategic necessity, areas identified for improvement, reactions to the rationalization plan, employee adaptation, and leadership’s central role in facilitating change. Findings point to both opportunities and challenges within institutional transformation, emphasizing the importance of effective communication, leadership engagement, and employee participation. Based on these results, the study proposes the framework consisting of resource optimization, adaptation, vision, enhancements, and the role of leadership to guide change processes (RAVER). The framework provides practical guidance for higher education leaders aiming to build a responsive and resilient organizational culture. This study contributes theoretical and practical insights by showing how phenomenological inquiry can enrich models of change management in Philippine higher education.